Cadmium metals particles-covered polystyrene nanospheres thin film material:fabrication, analysis and model - Nur, Hadi (2012)
It was well known that cadmium metals particles-covered 200 nm Polystyrene Nanospheres (PSNs) thin film material could be prepared from its according colloidal metals precursor of cadmium nitrate tetrahydrate, Cd(NO3)2.4H2O in water-polyvinil pyrrolidone (PVP) homogeneous mixture. After reducing it with sodium borohidride, NaBH4 then thin films of the colloidal were fabricated on a hydrophilic silicon wafer through gently dropping method and subsequently it was analyzed by both analytical isntruments of ATR-FTIR spectrometry and FESEM. It was clearly observed that wave number ranges of 1700-1600 cm-1 and 1500-1200 cm-1 generated signficant different ATR-FTIR spectra between pristine PSNs and cadmium-covered PSNs. In addition, surface morphology of pristine PSNs thin film explored with FESEM revealed sharply different from that of cadmium-covered PSNs one. It indicated that PSNs particles surface have succesfully been fully covered by cadmium metals particles. Therefore it could be concluded that cadmium metals particles-covered PSNs thin film could be fabricated from its according colloidal precursor and the model might be ilustrated as the following Fig. 2